THREE DIFFERENT TYPES OF PLASTIC PACKAGING MATERIALS: THEIR EFFECTS ON MOULD INFECTION AND AFLATOXIN CONTAMINATION IN PEANUTS. - Okky Setyawati Dharmaputra; Ina Retnowati; Santi Ambarwati (BIOTROPIA, 2007)
-